Discrimination of circulating tumor cells of breast cancer and colorectal cancer from normal human mononuclear cells using Raman spectroscopy - Ranc, Václav; Srovnal, Josef; Kvítek, Libor; Hajduch, Marian (The Analyst, 2013)
Circulating tumor cells present an important marker of the progress of several cancer diseases including breast and colorectal cancer, and enables an interesting prognosis and diagnostic options that can complement convenient diagnostic techniques based on several imaging methods. Based on its relevance, the analysis of such kinds of cells is within the scope of many research and clinical institutes; however, it still presents a difficult task. Here we used a state-of-the-art micro-Raman microscopic technique to enhance possibilities in the study of circulating tumor cells and their further differentiation. As cytospins present a convenient form of sample collection and preparation, we used this form of sampling as the initial point. Raman presents a non-destructive form of sample analysis and thus the samples can be further used for a method validation. We have considered the influence of fixation methods of the cells, where we found out that the ability of Raman spectroscopy to differentiate between three cell lines strictly depends upon the sample preparation method used. Namely breast (BT 549) and colorectal (HCT 116) circulating tumor cell lines and human mononuclear cells were compared. Methanol and paraformaldehyde methods of fixation were compared to simple drying out of the sample. It has been shown that drying out of the cells enables the best performance to be obtained in cell differentiation and this is demonstrated by the use of principal component analysis, where all three given cell lines were differentiated with a high level of confidence. Next, the cells were also scanned using 1 μm spatial resolution. The acquired data were visualized using both chemigrams and hierarchical clustering analysis.
Keywords: Colorectal Neoplasms; ženské pohlaví; leukocyty mononukleární; nádory prsu; nádorové cirkulující buňky; lidé; Ramanova spektroskopie; Breast Neoplasms; HCT116 Cells; Neoplastic Cells, Circulating; HCT116 buňky; Leukocytes, Mononuclear; Humans; Female; kolorektální nádory; Spectrum Analysis, Raman